A comparison between unifocal papillary thyroid microcarcinoma with noninvasive follicular thyroid neoplasm with papillary-like nuclear features and other patterns: A retrospective clinicopathological study - Emel Cakir; Ismail Saygin; Savas Kisioglu (Wolters Kluwer Medknow Publications, 2020)
Background: Papillary thyroid microcarcinoma (mPTC) is defined as a tumor with low malignancy potential. Different treatment protocols have been used at different centers for analyzing this tumor which has common recurrence and metastasis rates. Consequently, in 2016, the definition of noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP) was accepted which included the lesions > cm. It is important to explain the clinical course and appropriate treatment options for mPTC and its subtypes. Aims: In this study, we aimed to describe the clinical course of mPTC with and without NIFTP and to determine different risk groups among these subtypes. Material and Methods: We performed microscopic reexamination of about 280 unifocal mPTCs retrieved from our archives between 2007-2018 and analyzed the results of morphological and clinical comparison among these cases that had 0-11-years of clinical follow-up. Results: Among 280 unifocal mPTCs, 127 cases (45.4%) had classical morphology, 58 (20.7%) had NIFTP, 53 (18.9%) had infiltrative pattern, 27 (9.6%) had oncocytic pattern, 12 (4.3%) showed capsular invasion, and 3 (1.1%) showed other morphologies. Seven patients were detected with lymph node metastasis and one with distant metastasis at diagnosis. Lymph node metastasis (recurrence) was postoperatively detected in five patients. All patients with recurrence were women. Moreover, three of these patients were in their 30s and two in 70s. The median diameter of the tumor was 3 mm. Both invasive and noninvasive cases have recurred. Conclusion: Contrary to the results of the previous studies, the results of our study did not confirm the indolent course of mPTC with NIFTP. However, metastasis was detected both at the time of diagnosis and during the postoperative period. The malignancy potential of these tumors may not be low. Therefore, more clinicopathological and molecular studies are needed to determine the biological behavior of mPTC cases with different histology.